6x2-2x-6=0

Simple and best practice solution for 6x2-2x-6=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x2-2x-6=0 equation:



6x^2-2x-6=0
a = 6; b = -2; c = -6;
Δ = b2-4ac
Δ = -22-4·6·(-6)
Δ = 148
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{148}=\sqrt{4*37}=\sqrt{4}*\sqrt{37}=2\sqrt{37}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-2\sqrt{37}}{2*6}=\frac{2-2\sqrt{37}}{12} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+2\sqrt{37}}{2*6}=\frac{2+2\sqrt{37}}{12} $

See similar equations:

| 9p=63# | | 9^1-x=27^x-1 | | -38=2(2x-4)+10 | | 3x-4x+11=4+-4x6x | | 4^x+1=2^x | | 2(3x-2)=5x-6 | | 3(3x-2)=-15 | | 27^1-x=3 | | 2(2x-2)=x-13 | | 4x+28=5(3x-1) | | 4x3=108 | | -3x+30=3(3x-2) | | -4x+33=x-32 | | 5x+3=10x-17x | | -36=2(5x-1)+6 | | 5x-19=-4x+44 | | 3^x=27^2-3x | | 36^x-3=216 | | 5^5x-2=125 | | 9^2x=27 | | 2(6-3x)=(1+2x)/3 | | 5+x2=32-2x2 | | x+5(x-12)=90 | | 0=29.626+2a(1.5) | | 6^-x=1/216 | | 90-x=(180-x)/5 | | 1/4x+1/3x=7/4 | | Y=√25x^2-6x+7 | | 2,5x+40=5x | | Y=25x^2+6x+7 | | 7^2x=49 | | f(-2)=3(-2)^2+5(-2)-9 |

Equations solver categories